Does government precommitment promote environmental innovation? - Emmanuel Petrakis; Anastasios P. Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper investigates the effect of credibility of environmental policies on environmental innovation and welfare. When the government precommits to an emission tax, the monopolist's abatement effort is lower than if the environmental policy is at the government's discretion. Time consistent emission tax is lower than optimal emission tax under precommitment. Finally, welfare is always higher if the government can commit to an emission tax.
Keywords: L12; Q25; Q28; 330; Monopoly; Non-credible policies; Precommitment; Emission Tax; Abatement effort; Glaubwürdigkeit; Umweltpolitik; Wohlfahrtsanalyse; Umweltschutzinvestition; Investitionsentscheidung; Monopol; Theorie